The Effect Of Literacy, Financial Inclusion, Lifestyle, And Environment On The Rise Of Illegal Online Loans Through Easy Transactions Among The Community - Yuannisa, Rizka Adlia; Rokan, Mustafa Kamal; Batubara, Maryam (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The value of fintech lending, also known as online lending (pinjol), in Indonesia has increased for three consecutive months from July to September 2023. Due to the ease of access, various illegal online loans have sprung up. The type of research used in this study is quantitative research. This correlation study was conducted by researchers to determine the level of relationship between two or more variables, without making any changes. Overall, the prevalence of illegal online loans among the public is greatly influenced by financial literacy, financial inclusion, and lifestyle, with ease of transaction as the main mediator. The social environment does not play a significant role in this context. To reduce the negative impact of illegal online loans, a combination of increased literacy, wise financial inclusion regulations, control of consumptive lifestyles, and strict regulations on the ease of transactions on online lending platforms is needed.